2019
DOI: 10.1101/595900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Larvicidal evaluation of the Origanum majorana L. Essential Oil against the larvae of the Aedes aegypti mosquito

Abstract: This study evaluated the larvicidal activity of O. majorana essential oil, identified the chemical composition, evaluated the antimicrobial, cytotoxic and antioxidant potential. The larvicidal activity was evaluated against larvae of the third stage of Aedes aegypti, whereas the chemical composition was identified by gas chromatography coupled to mass spectrometer, the antimicrobial activity was carried out against the bacteria Pseudomonas aeruginosa, Escherichia coli and Staphylococcus auereus, the antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The average percentage of free-radical scavenging activity of essential oils and the reference standard (ascorbic acid) by DPPH assay is shown in Figure 4a,b. According to a literature review, O. majorana EOs were found to exhibit stronger antioxidant activity in terms of smaller IC 50 values, smaller than 200 µg/mL [14,21,63,[73][74][75]. In other studies, antioxidant activity of marjoram EO was reported to be weaker, with IC 50 values greater than 200 µg/mL [41,68,76,77].…”
Section: Antioxidant Activity 261 Dpph Free Radical Scavenging Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The average percentage of free-radical scavenging activity of essential oils and the reference standard (ascorbic acid) by DPPH assay is shown in Figure 4a,b. According to a literature review, O. majorana EOs were found to exhibit stronger antioxidant activity in terms of smaller IC 50 values, smaller than 200 µg/mL [14,21,63,[73][74][75]. In other studies, antioxidant activity of marjoram EO was reported to be weaker, with IC 50 values greater than 200 µg/mL [41,68,76,77].…”
Section: Antioxidant Activity 261 Dpph Free Radical Scavenging Activitymentioning
confidence: 99%
“…The essential oil of this plant has also been used for pain, gastrointestinal problems, and respiratory tract disorders [19,20]. The antiparasitic and larvicidal activities of marjoram have also been reported in several studies [21]. Moreover, majorana was reported to show antidiabetic activity [22], nephrotoxicity protective effects [23], anti-inflammatory, analgesic, and anti-pyretic activities [24].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that after administering 250 mg and 500 mg/kg of chicory seed extract, its cardioprotective effects were observed through inhibition of inflammatory response and oxidative stress. A study was conducted to determine the larvicidal activity of chicory against the mosquito vectors of dengue fever, malaria, and filariasis 100 A study was conducted to test and determine the antibacterial effect of O. majorana essential oil against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa 103 . For this, 2000 µg/ml of essential oil was tested against a standard of 50 µg/ml of amoxicillin and a control of 2% DMSO.…”
Section: Fig 33: Liquorice Fig 34: Phytoconstituents Of Liquoricementioning
confidence: 99%
“…In this context, many studies found that O. majorana ameliorated human cancer cell lines’ growth, including human lymphoblastic leukemia cell lines, human hepatoma cell lines, in addition to experimentally induced fibrosarcoma, lung carcinoma, and hormone-dependent prostate carcinoma [ 24 , 27 , 28 ]. Previous reports also revealed the potent antiproliferative impact of O. majorana on colon cancer cells through triggering apoptosis with mitochondrial dysfunction [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%